Direitos humanos sem fundamentos? uma abordagem retórica dos discursos de (DES) legitimação no (PÓS) moderno - Albano, Maria Luiza Caxias (2017)
Human rights have been a widely debated topic in the contemporary world, and therefore, has become a complex plot for analysis. In this sense, the present work is dedicated to the philosophical assumptions of human rights based on the processes of (dis)legitimation in the postmodern. There is, therefore, a need for a revision of the epistemological foundations that have legitimated the modern, and therefore have shaped the modern conception of human rights. From the revision of some dimensions of modernity, which includes the movement of legitimation of this paradigm, to the movements of delegitimation in the postmodern, I highlight ways of revising the approach regarding human rights discourses from the methodological and rhetorical use language games. I therefore have a network of discourses concerning not only human rights but also those discourses that touch but not yet assimilated by the classical epistemological bases of human rights, as well as reconsiderations about the (im) possible models of human rights.